2016
DOI: 10.1155/2016/8253090
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Narrow Diameter Implants in the Molar Area

Abstract: Implant rehabilitations in the posterior jaw are influenced by many factors such as the condition of the remaining teeth, the force factors related to the patient, the quality of the bone, the maintenance of the hygiene, the limited bone height, the type and extent of edentulism, and the nature of the opposing arch. The gold standard is to place a regular diameter implant (>3.7 mm) or a wide one to replace every missing molar. Unfortunately, due to horizontal bone resorption, this option is not possible withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Thus, the bone thickness in the second premolar area appears to be more consistent from coronal to apical, which means it is more constant than on the first premolar, meeting the results obtained by Shen et al [32]. These results confirm that in the apical direction, bone availability is not always superior, which disturbs the achievement of implant primary stability and might indicate the need for employing bone regeneration techniques prior to implant placement or using narrow diameter implants (< 3.5 mm) [16,21,28,33,44].…”
Section: Discussionsupporting
confidence: 78%
“…Thus, the bone thickness in the second premolar area appears to be more consistent from coronal to apical, which means it is more constant than on the first premolar, meeting the results obtained by Shen et al [32]. These results confirm that in the apical direction, bone availability is not always superior, which disturbs the achievement of implant primary stability and might indicate the need for employing bone regeneration techniques prior to implant placement or using narrow diameter implants (< 3.5 mm) [16,21,28,33,44].…”
Section: Discussionsupporting
confidence: 78%
“…Research reports satisfactory survival rates, patient‐centered outcomes and certain complications of NDI‐supported prostheses . In addition, some researchers investigated clinical outcomes of NDIs into the posterior jaws and reported 100% success rate . Recent systematic reviews and meta‐analyses revealed comparable clinical and radiographic status of NDIs and RDIs including in posterior load‐bearing regions …”
Section: Introductionmentioning
confidence: 99%
“…Saad M et al. (Saad, Assaf & Gerges, ) reported a clinical study, in which 11 NDIs were placed into 10 patients to replace missing molars, with an observed success rate of 100%. The mean follow‐up time was 4.2 years.…”
Section: Introductionmentioning
confidence: 99%